Luminescent coordination polymers constructed using a mixed-ligand strategy for highly selective luminescence sensing of nitrobenzene, Fe3+ and Cr2O72− ions and photodegradation of rhodamine B. Issue 27 (1st July 2020) - Wang, Jun-Jie; Wu, Fei-Fan; Su, Ning; Li, Pan-Pan; Wang, Si-Yin; Ma, Hui-Yan; Li, Yun-Wu; Yu, Mei-Hui
Abstract : Using a mixed ligand strategy, ten new LCPs were constructed. They all display highly sensitive and selective luminescence sensing for NB, Cr2 O7 2− and Fe 3+ ions. Moreover, 3–10 also exhibit high photocatalytic activities toward the degradation of RhB. Abstract : Using a mixed ligand strategy, ten new luminescent coordination polymers (LCPs), namely, [Cd(IPA-NH2 )(Htpim)] n (1 ), [Mn(IPA-NH2 )(Htpim)] n (2 ), [Zn(IPA-OH)(Htpim)] n (3 ), [Cd(IPA-OH)(Htpim)] n (4 ), [Zn(Htpim)2 (H2 O)2 ](IPA-OH) n (5 ), [Cd(Htpim)2 (H2 O)2 ](IPA-OH) n (6 ), [Cd(IPA-NO2 )(Htpim)] n (7 ), [Zn2 (PMA)(Htpim)2 ] n (8 ), [Cd2 (PMA)(Htpim)2 ] n (9 ) and [Cu(H2 PMA)(Htpim)2 (H2 O)] n (10 ) (Htpim = 2, 4, 5-tri(4-pyridyl)-imidazole, H2 IPA-NH2 = 5-aminoisophthalic acid, H2 IPA-OH = 5-hydroxyisophthalic acid, H2 IPA-NO2 = 5-nitroisophthalic acid, H4 PMA = 1, 2, 4, 5-benzenetetracarboxylic acid) were constructed. Compounds 1–4 and 7–9 have similar 2D 4 4 networks, while 5, 6 and 10 show 1D chain structures. The results reveal that the coordination configuration of M(ii ), carboxylic acids, and coordinated water molecules play pivotal roles in the formation of the final structures. Moreover, the selective luminescence sensing and photocatalytic performances of 1–10 were also studied. Interestingly, they can sensitively detect trace amounts of nitrobenzene (NB), Cr2 O7 2− or Fe 3+ through luminescence quenching. In addition, 3–10 show high photocatalytic activities toward the degradation of rhodamine B (RhB).